2013
DOI: 10.1007/s10555-013-9456-2
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer microenvironment: implications for cancer dissemination and chemoresistance acquisition

Abstract: Ovarian adenocarcinoma is characterized by a late detection, dissemination of cancer cells into the whole peritoneum, and the frequent acquisition of chemoresistance. If these particularities can be explained in part by intrinsic properties of ovarian cancer cells, an increased number of studies show the importance of the tumor microenvironment in tumor progression. Ovarian cancer cells can regulate the composition of their stroma in promoting the formation of ascitic fluid, rich in cytokines and bioactive lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
172
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(175 citation statements)
references
References 192 publications
1
172
1
1
Order By: Relevance
“…It has been widely reported that IL-6 and IL-8 reinforce the proliferation of ovarian cancer cells (11). However, the present study demonstrated that IL-6 and IL-8 did not affect ovarian cancer A2780 cell proliferation (Fig.…”
Section: Proliferation Of Ovarian Cancer Cells Following Stimulation contrasting
confidence: 54%
See 1 more Smart Citation
“…It has been widely reported that IL-6 and IL-8 reinforce the proliferation of ovarian cancer cells (11). However, the present study demonstrated that IL-6 and IL-8 did not affect ovarian cancer A2780 cell proliferation (Fig.…”
Section: Proliferation Of Ovarian Cancer Cells Following Stimulation contrasting
confidence: 54%
“…The key cytokines in this regulation appear to be interleukins-6 and 8 (IL-6 and IL-8), since increased levels of these cytokines have been identified in the ascites fluid of ovarian cancer patients (10,11). In vitro IL-6 is secreted by mesothelial cells, fibroblasts, macrophages and ovarian tumour cells, while IL-8 is secreted by endothelial cells and mesothelial cells, monocytes and ovarian tumour cells (11). Therefore, the tumour microenvironment is significant in all processes of ovarian cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Selective ET A R blockade could tilt the balance toward ET B R signaling in the tumor microenvironment, including the recruitment of antitumor T cells (10,11). Besides the intrinsic mechanisms activated in EOC cells, acquisition of chemoresistance could be dependent also by the tumor microenvironment (44). In this regard, recent studies demonstrated that endothelial cells chemoprotect tumor cells through activation of ET-1 axis (45).…”
Section: Discussionmentioning
confidence: 99%
“…The ovarian tumor microenvironment, which is composed primarily of fibroblasts, ECM proteins, endothelial cells, and lymphocytic infiltrates, can regulate tumor growth, angiogenesis, dissemination, and chemoresistance (11,16). CAFs have been shown to play crucial roles in cancer progression.…”
Section: Cafs Upregulate Lpp In Mecsmentioning
confidence: 99%